Wdr47, Camsaps, and Katanin cooperate to generate ciliary central microtubules - Hao Liu (Nature Portfolio, 2021)
Ciliary beating is mediated by the axonemal central pair microtubules, though how these non-centrosomal microtubules form is poorly understood. Here the authors show that a trio of proteins act cooperatively to initiate central microtubule formation in mammals.